“SELEKTIFITAS SPECIES” ALAT TANGKAP GARUK DI CIREBON, JAWA BARAT - Wiyono, Eko Sri (Bumi Lestari, 2009)
In order to understand the fishing gear characteristics of “garuk”, a traditional fishing gear in North Java Sea, study about species selectivity of garuk has been conducted in Cirebon, West Java. Using Shannon-Diversity Index and Dominance Index analysis the catch diversity and dominancy were analyzed. The result analysis showed that the number of species diversity of garuk varied between 0.8 – 1.2. On the other hand, result analysis of dominance index showed that the number varied between 0.3 – 0.5. This result indicated that garuk has low selectivity to target species.
Keywords: diversity; dominancy; garuk; species; selectivity